Surface plasmon polariton assisted optical pulling force. Issue 1 (23rd December 2015) - Petrov, Mihail I.; Sukhov, Sergey V.; Bogdanov, Andrey A.; Shalin, Alexander S.; Dogariu, Aristide
Abstract : The authors demonstrate the generation of attractive optical force acting on nanoparticle in the vicinity of metal surface due to surface plasmon polariton (SPP) excitation. The excitation of SPP has strongly asymmetrical character which is determined by spin–orbit coupling of the induced rotating dipole and SPP mode. As a result of the total momentum conservation, the force acting on the particle points in a direction opposite to the incident wave propagation. This effect can be utilized for effective optomechanical control of nanoobjects over metallic surface. Abstract: We demonstrate both analytically and numerically the existence of optical pulling forces acting on particles located near plasmonic interfaces. Two main factors contribute to the appearance of this negative recoil force. The interference between the incident and reflected waves induces a rotating dipole with an asymmetric scattering pattern, while the directional excitation of surface plasmon polaritons (SPPs) enhances the linear momentum of scattered light. The strongly asymmetric SPP excitation is determined by spin–orbit coupling of the rotating dipole and surface plasmon polariton. As a result of the total momentum conservation, the force acting on the particle points in a direction opposite to the incident wave propagation. We derive analytical expressions for the force acting on dipolar particles placed in the proximity of plasmonic surfaces. Analytical expressions for this pulling force are derived within the dipole approximation and are in excellent agreement with results of electromagnetic numerical calculations. The forces acting on larger particles are analyzed numerically, beyond the dipole approximation.